KUALITAS LAYANAN DAN HARGA SEBAGAI PENENTU KEPUTUSAN PEMBELIAN MINUMAN KOPI - Khusaini Khusaini; Siti Nurul Mawaddah; Aniek Widiarti (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2021)
Purchasing decision is the process of consumers who will make a purchase of a product, taking into account the various alternative options available to produce a choice that is considered the most appropriate for the product that consumers will buy. We used cosumers of the Starbucks Coffee Tangcity Mall Tangerang and Starbucks Coffee DT Cipondoh as the infinite populations. The samples size were 96 unit by simple random technique. Collecting data using a questionnaire that has been valid and reliable. The data analysis technique is simple linear regression. The results showed that the service quality and price determined significantly to the starbucks consumer purchasing decisions. In contrats, brand image had no effect on it. The findings of the cuurent research contribute to the improvement of consumer behavior literature. The empirical contribution is in the form of the importance of boosting and taking care of the quality of sales services.